ASAL-USUL BUDAYA KEPULAUAN TELLO DITINJAU DARI SISI PAKAIAN ADAT PERNIKAHAN - ZAI, EKA PERIAMAN (JURNAL EDUCATION AND DEVELOPMENT, 2018)
Tello Islands is a small island located in South Nias Regency and separated from the mainland of Nias Island. Although included in the Nias tribe category, Tello Islands have a lot of diversity in terms of culture. it can be seen from the traditional wedding attire wears by the local community which is very unique and similar to traditional Minang clothing. In the traditional dress, the bridegroom wears keris, songket cloth wrapped around the waist of the groom, hat (takula), while traditional bridal clothes in other areas of the Nias Islands do not use it. To find out the origins of Tello Island Culture in terms of traditional clothing, researchers conducted research using qualitative research with descriptive approach methods. Researchers conducted interviews with the local community, especially in the case of traditional wedding clothes and documented parts of traditional clothing. From the observations, documentation and interviews found in the field, it turned out that the Tello Islands culture originated from the Nias Islands and is still maintained to this day, although there are certain parts of the traditional dress of male and female marriage that have changed and there are also clothing parts which is no longer used. This is because the production of parts of traditional clothing is no longer there and symbolic interaction, the bride is symbolized as queen and king a day